Coadministration of clozapine and fluvoxamine in psychotic patients - clinical experience - Lammers, Claas-Hinrich; Deuschle, Michael; Weigmann, Harald; Härtter, Sebastian; Hiemke, Christoph; Heesen, Christoph; Heuser, Isabella (Pharmacopsychiatry, 2007)
Thieme E-Books & E-Journals
Online: 20. April 2007
Gesehen am 16.11.2020